2012
DOI: 10.1159/000339589
|View full text |Cite
|
Sign up to set email alerts
|

Localized and Sustained Delivery of Fibroblast Growth Factor-2 from a Nanoparticle-Hydrogel Composite for Treatment of Spinal Cord Injury

Abstract: After traumatic spinal cord injury, grossly injured blood vessels leak blood and fluid into the parenchyma, leading to a large cystic cavity. Fibroblast growth factor-2 (FGF2) can reduce immediate vasoconstriction of vessels in the tissue surrounding the primary injury and promote angiogenesis. A localized delivery system would both achieve restricted delivery of FGF2 to the spinal cord and limit possible systemic effects such as mitogenesis. To enhance the endogenous angiogenic response after spinal cord inju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
40
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(40 citation statements)
references
References 53 publications
0
40
0
Order By: Relevance
“…Furthermore, a comparative study of four methacrylate hydrogels indicated that the HEMA-MOETACl hydrogel was the best carrier of mesenchymal stem cells (MSCs) in vitro and in vivo 29 . The HAMC hydrogel and the composite of HAMC/PLGA have also been shown to be excellent delivery systems where biomolecules are delivered directly to the injured spinal cord 15,33 . These findings indicate that a suitable hydrogel, combined with appropriate neurotrophic factors or stem cells seems to be a promising approach in the treatment of SCI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, a comparative study of four methacrylate hydrogels indicated that the HEMA-MOETACl hydrogel was the best carrier of mesenchymal stem cells (MSCs) in vitro and in vivo 29 . The HAMC hydrogel and the composite of HAMC/PLGA have also been shown to be excellent delivery systems where biomolecules are delivered directly to the injured spinal cord 15,33 . These findings indicate that a suitable hydrogel, combined with appropriate neurotrophic factors or stem cells seems to be a promising approach in the treatment of SCI.…”
Section: Discussionmentioning
confidence: 99%
“…bFGF is abundantly expressed in the nervous system, where it has vital roles, and was previously shown to support the survival and growth of neurons and neural stem cells in vitro 14 . After SCI, seriously injured blood vessels leak blood and fluid into the parenchyma, leading to a large pseudocyst cavity, and bFGF can decrease immediate vasoconstriction of blood vessels in the tissue near the epicenter of the injury and promote angiogenesis 15 . Previous findings have also shown that bFGF infusion or transgene therapy may promote the regeneration of neurons and axons 16,17 .…”
mentioning
confidence: 99%
“…Intrathecal administration typically involves osmotic pumps to continuously deliver FGF to (or near) the lesion over days or weeks Kojima & Tator, 2002;Lee et al, 1999;Rabchevsky et al, 1999). FGF has also been delivered in association with Schwann cells or peripheral nerve (PN) grafts, released by carriers such as gelfoam, gelatin, fibrin glue, HEMA-MOETACL hydrogels alginate scaffolds or from nanoparticles (Chen et al, 2015;Furuya et al, 2013;Grulova et al, 2015;Guzen et al, 2012;Kang et al, 2013;Lee et al, 2008Lee et al, , 2010Meijs et al, 2004;Meng et al, 2008;Shin et al, 2014;Tsai et al, 2006;Wu et al, 2008). A recent study successfully delivered FGF2 (a known mitogen for stem cell self-renewal) via subcutaneous injection to give improved outcomes (Goldshmit et al, 2014).…”
Section: Fibroblastic Growth Factorsmentioning
confidence: 99%
“…Changes in astrocyte phenotype after FGF administration to the injured spinal cord are not always extensive (Kang et al, 2013;Kim et al, 2006), although FGF2 (Grulova et al, 2015) and FGF1 (Lee et al, 2008) may reduce astrocytic reactivity and macrophage infiltration. In zebrafish SCI studies (Goldshmit et al, 2012), subcutaneous administration of FGF2 in adult mice reduced inflammation, microglia and macrophage activation, and astrocyte reactivity at 2 weeks.…”
Section: Fibroblastic Growth Factorsmentioning
confidence: 99%
“…However, as with chondroitinase ABC (chABC), the method of delivery to the spinal cord lesion utilized in many of these studies is not effectively translated to use in humans. Since these factors will be needed for extended periods of time, they can be incorporated into nanoparticles as well as hydrogels or scaffolds for sustained release [Baumann et al, 2010;Stanwick et al, 2012;Kang et al, 2013;des Rieux et al, 2014;Elliott Donaghue et al, 2014. Some of these formulations could potentially function to both stimulate and guide axon regrowth along a specific path though the spinal cord.…”
Section: Nanoparticles As Therapeutics In the Spinal Cordmentioning
confidence: 99%